Toward High-Speed Imaging of Cellular Structures in Rat Colon Using Micro-optical Coherence Tomography - Yu, Xiaojun (2017)
The mucosal microanatomy of the large intestine is characterized by the presence of crypts of Lieberkühn, which is associated predominantly with goblet cells. Such cellular-level intestinal microstructures undergo morphological changes during the progression of bowel diseases, such as colon cancer or ulcerative colitis. As an indicator of gastric cancers, intestinal metaplasia in the large intestine is characterized by the appearance of goblet cells in gastric epithelium, and therefore, visualization of intestinal microstructure changes in cross-sectional view, particularly in vivo, in a high-speed fashion would assist early disease diagnosis and its treatment. In this paper, we investigated the capability of micro-optical coherence tomography (μOCT) for high-speed cellular-level crypt and goblet cell structures imaging ex vivo and in vivo . The adopted μOCT system achieved a resolution of 2.0 μm in both the lateral and axial directions in air. Ex vivo and video-rate in vivo images acquired in 3-D at respective imaging rates of 20 and 60 frames/s are presented and compared with the histology images. Imaging results show that the detailed microstructures, such as the crypt lumen and the goblet cells, could be clearly identified and are also comparable with those in histology images. Such comparisons also indicate that high-resolution μOCT could be a powerful tool to perform “optical biopsy” in colorectal tissue. This is the first work, to the best of our knowledge, on cellular-level structure imaging in intestinal mucosa using spectral-domain OCT.